Index and the body of philosophy on Derrida's 'Performances Without Presence' - Bekavac, Luka (2006)
The article attempts to examine certain properties of indexing against the backdrop of Derrida's notion of writing. Possibility of performative in the "presenceless" ontology of text is presented as an irreducible obstacle to the paratextual work of index as a tool of logocentric closure.
ENG